2009
DOI: 10.1007/s12017-009-8101-2
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Flux Across the Blood–Brain Barrier

Abstract: Manganese (Mn) is essential for brain growth and metabolism, but in excess can be a neurotoxicant. The chemical form (species) of Mn influences its kinetics and toxicity. Significant Mn species entering the brain are the Mn(2+) ion and Mn citrate which, along with Mn transferrin, enter the brain by carrier-mediated processes. Although the divalent metal transporter (DMT-1) was suggested to be a candidate for brain Mn uptake, brain Mn influx was not different in Belgrade rats, which do not express functional DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 136 publications
(167 reference statements)
2
82
0
Order By: Relevance
“…In biological systems, Mn 2ϩ has the same charge and relative size as Ca 2ϩ , and a number of reports have shown that Mn and Ca trafficking, recruitment, and storage are regulated by the same ion pumps and intracellular compartments. Therefore, Mn 2ϩ might compete with Ca 2ϩ in uptake studies (59,60), thereby disturb intracellular Ca homeostasis and correct tight junction formation and/or localization (26,61). This effect might be reversible by elevated Ca concentrations, as indicated by the present occludin immunofluorescence studies.…”
Section: Discussionmentioning
confidence: 75%
“…In biological systems, Mn 2ϩ has the same charge and relative size as Ca 2ϩ , and a number of reports have shown that Mn and Ca trafficking, recruitment, and storage are regulated by the same ion pumps and intracellular compartments. Therefore, Mn 2ϩ might compete with Ca 2ϩ in uptake studies (59,60), thereby disturb intracellular Ca homeostasis and correct tight junction formation and/or localization (26,61). This effect might be reversible by elevated Ca concentrations, as indicated by the present occludin immunofluorescence studies.…”
Section: Discussionmentioning
confidence: 75%
“…Some evidence indicates that both transferrin receptor 1 (TfR1) and the divalent metal transporter 1 (DMT1) contribute to Mn transport across the BBB [45,46]. Other transporters have been reported to possess an ability to transport Mn.…”
Section: Tyrosine Hydroxylase Is Altered Upon Olfactory Mn Exposures mentioning
confidence: 99%
“…These facts can also lead to increases in the bioavailability of pollutants in the environment and, consequently, the metal uptake rates and their toxicity (Bervoets et al, 1996;Vergauwen et al, 2013;Lee et al, 2014). Manganese (Mn 2+ ) is a constitutive element of a series of essential enzymes and cofactors that are fundamental to brain function, such as glutamine synthetase, superoxide dismutase and others (Yokel, 2009), but it can be very toxic at concentrations above the optimal threshold level (Vieira et al, 2012). In natural waters, dissolved manganese from anthropogenic sources/influences associated with metal mining and other industrial activities may reach very high concentrations (McNeely et al, 1979;Morillo, Usero, 2008).…”
Section: Introductionmentioning
confidence: 99%